Studies of Improving Drinking Water Quality in the Kalurahan Banaran Kabupaten Kulon Progo Using Porous Concrete Filter - Arviananda, Rr. Dita; Kamulyan, Budi; Nurrochmad, Fatchan (Universitas Negeri Yogyakarta, 2023)
Some citizens of the Kalurahan Banaran Kabupaten Kulon Progo everyday use water that has an iron content (Fe) of 8.8 mg/L and a turbidity of 120 NTU, which is above the limit set by the Minister of Health's Regulation RI Number: 2 Tahun 2023 on the Quality Requirements of Drinking Water. To solve this problem, research has been conducted to reduce Fe and turbidity by using porous concrete filters. Three models of porous concrete A (porousity 0.42), B (porousity 0.44), and C (porousity 0.46), were used to filter water samples using two aerator diffusers at speeds of 3 L/h and 6 L/hour on each porous concrete filter. The results of the study showed that at an aeration rate of 3 L/hour, there had been a successive decrease in turbidity and Fe from 14.9 NTU to 1.38 NTU and 1.64 mg/L to 0.14 mg/L (filter A); 80 NTU to 0.5 NTU and 6.55 mg/L to 0.02 mg/L (filter B); 80 NTU to 0.1 NTU and 6.5 mg/L to 0 mg/L (filter C). For an aeration rate of 6 L/hour, there had been a successive decrease in turbidity and Fe from 80 NTU to 0.82 NTU and 6.55 mg/L to 0.05 mg/L (filter A); 89.8 NTU to 0.28 NTU, and 7.8 mg/L to 0.01 mg/L (filter B); 80 NTU to 0.28 NTU and 6,55 mg/L to 0 mg /L (filter C). The results show that the porous concrete filter can be considered an alternative to drinking water treatment in the Kalurahan Banaran Kabupaten Kulon Progo.